Kajian Kelayakan Struktur Bangunan Pasca Kebakaran (Studi Kasus Gedung Pasar Koppas) Kota Padang - Elvi Roza Syofyan; Syaiful Amri -; Munafri Alwys - (Jurnal Ilmiah Poli Rekayasa, 2014)
In a feasibility study of the structure after the fire ( Case Study Building of Pasar Koppas in  Padang ) . To obtain preliminary data, building data includes tracking information about the building construction has been done. Then visual inspection includes examination of the structural system of the building and non-structural components, as well as the configuration of the geometry component of the structure. Measurement of the building is intended to determine the configuration of the building . It can also serve as a confirmation of the existing building geometric conditions . Later examination of the damage structure and non- structural components by visual observation . Field trials conducted to obtain the data quality of the material structure of the building, with a non destruxctive and destructive . This activity is a test of the quality of the concrete surface with a hammer concrete test, concrete homogeneity measurement, measurement of the diameter and spacing of reinforcement, concrete cored drill with the core drill tools, observations reinforcement fatigue . While in the laboratory to test the compressive strength of the concrete core and reinforcement tensile test. Taking photographs of the condition of the buildings, structural components and non-structural components for further examination to determine the location of the damage, as well as a guide to determine damage level of the building, in addition to the photographs can serve as documentation . Then the data evaluation and analysis of the structure of the building . From the results of the evaluation and analysis of the feasibility of building structures from Pasar Koppas could be concluded, that the structure and function of the building is still viable . For the convenience of occupancy necessary to repair or retrofitting the proper manner and method by the Government of Padang City.